Sikap Konsumen Terhadap Atribut Produk Kopi Coffee Campus di Kota Bandar Lampung - Kusmaria; Annisa Fitri (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
The coffee shop industry is growing along with the increasing consumer interest in coffee-based beverage products. To win the coffee shop market competition, a marketing strategy can be considered by analyzing consumer behaviour through consumer attitudes towards products. This research looked at consumer attitudes towards Coffee Campus coffee products in Bandar Lampung City in 2021. A sample of 33 people was taken towards coffee consumers at Coffee Campus using the accidental sampling method. The data analysis method used is the Fishbein method, which analyzes the attributes of coffee products, including the belief variable and the evaluation variable of interest (evaluation). Research on consumer attitudes towards the characteristics of coffee campus coffee products in Bandar Lampung City gives the result that consumer attitudes towards coffee product attributes, which include taste, taste variants, product packaging, product design, product quality, brands, labels and service at the Coffee Campus coffee shop significantly overall have an optimistic category.